Cricket, commerce, and public health: promotion of tobacco, alcohol, and high in fat, sugar, and salt products - Prashant Kumar Singh; Prashant Kumar Singh; Rupal Jain; Vandana Tamrakar; Sanchita Roy Pradhan; Sagarika Rout; Sagarika Rout; Chandresh Pragya Verma; Amit Yadav; Upendra Bhojani; Yatan Pal Singh Balhara; Shalini Singh (Frontiers in Digital Health)
BackgroundIncreasing incidences of non-communicable diseases globally present a major public health challenge, with tobacco, alcohol, and ultra processed food products high in fat, sugar, and salt (HFSS) contributing significantly to this epidemic. Despite regulatory efforts, loopholes persist, allowing companies to promote such products through surrogate advertisements and new media platforms. This study investigates advertisements aired during the Men's Cricket World Cup 2023 on the Over-the-Top (OTT) platform.MethodsA comprehensive analysis of advertisements aired during the World Cup matches on OTT platform during October-November 2023 was undertaken to assess the extent and type of advertising of alcohol, tobacco and HFSS products. A standardized observation protocol was followed, documenting the frequency, type, and celebrity featured in each advertisement. The observed advertisements were categorized into six segments including surrogate tobacco and alcohol, soft drinks, energy drinks, edible products commonly consumed by children, and other edibles/beverages.ResultsObservations show that 80.9% (n = 1,769) of total advertisements promoted tobacco, alcohol and HFSS products. Notably, surrogate tobacco advertisements were predominantly displayed during matches involving the Indian team, accounting for 86.7% of the total surrogate tobacco advertisements. Edible products commonly consumed by children comprised 60.6% of unhealthy advertisements during over-breaks. Celebrity endorsements, particularly by Bollywood actors and Indian cricketers were common.ConclusionObservations reveal a concerning prevalence of advertisements promoting tobacco, alcohol, and HFSS products. Children emerged as a particularly vulnerable target for advertisement-induced consumption behaviors. These findings highlight the need for stricter regulations and effective enforcement to curb the promotion of unhealthy products.